The Physical Health Condition and Health Promotion Program for Female Students at Shanghai University of Finance and Economics - Shuyang, An; Eakronnarongchai, Wiradee; Duangkam, Jakrin (Journal of Roi Kaensarn Academi, 2024)
The declining physical health of female college students, vital to talent development and the nation’s future, highlights the urgent need for action in college physical education. This study aims to assess the physical health of female students at Shanghai University of Finance and Economics, identify key factors influencing their health through fitness tests and questionnaires, and propose evidence-based strategies for improvement. The primary objective of this study is to assess the physical health status of female students at Shanghai University of Finance and Economics. The survey targets 300 female students from grades one to three, while the experimental subjects include 54 freshman female students from the same university. This study understands their health status and identifies influencing factors. Methods used include literature review, expert interviews, questionnaires, experiments, tests, and statistical analysis. The study analyzed test results and exercise habits to identify health factors and proposed strategies to enhance their health based on relevant theories and Shanghai University of Finance and Economics’ teaching practices. The results of the study were as follows: The physical health test results show that most female students achieve a passing level, indicating a need for increased exercise. Freshman girls need to improve vital capacity, flexibility, standing long jump, and one-minute sit-up scores, while juniors need to enhance 50-meter and 800-meter run performances. Poor health levels are due to individual and external factors, such as lack of interest in sports and inadequate physical education facilities. This study reveals progress in flexibility and endurance among female students at Shanghai University of Finance and Economics but highlights challenges in strength, speed, and consistent exercise habits. Gender-specific patterns and environmental barriers call for tailored interventions, improved facilities, and targeted training. Comprehensive reforms in physical education are essential to address these gaps and promote holistic student health and development.